Sero-epidemiological survey of brucellosis in small ruminants in Hamedan province, Iran - Gharekhani, Jamal; Rasouli, Mahmoudreza; Abbasi-Doulatshahi, Ehsan; Bahrami, Mohammadali; Hemati, Zahra; Rezaei, Aliakbar; Shahreiari, Aboulghasem (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Brucellosis is a highly contagious zoonosis with global distribution. The disease remains endemic in many countries including Iran, while its seroprevalence in endemic area is not well documented. We aimed to determine the seroprevalence of brucellosis in sheep and goats in Hamedan province, west of Iran. Material and methods: A total of 3,250 blood samples from 2,550 sheep and 700 goats were collected randomly. All samples were analyzed for the presence of Brucella antibodies using Rose Bengal, Wright standard tube agglutination and 2-mercaptoethanol agglutination tests. Results: The seroprevalence rate of brucellosis in animals and flock level were found in 4.6% and 13.6% of goats and 3% and 27.9% of sheep, respectively. No evidence of correlation between gender and Brucella infection rate were found in animals (P>0.05). Statistical significant differences was seen between age groups and infection rate in goats (P=0.033, OR=2.1); unlike to sheep (P=0.373). Also, the infection rate in nomads population of sheep was higher than fix location animals (P=0.003; OR=1.9); unlike to goats (P=0.195). In animals with history of abortion and vaccination against brucellosis, seroprevalence rate was significantly lower than other (P<0.05). Conclusion: This is the first report of brucellosis in sheep and goats in Hamedan province. The design of a comprehensive control program including vaccination, screening, and culling of brucellosis-positive animals is recommended. http://doi.org/10.5455/javar.2016.c179